Analysis on the Coupling Effect of Xi'an-Yinchuan High Speed Railway and Economy Development in Shanxi-Gansu-Ningxia District Railway and Economy Development in Shanxi-Gansu-Ningxia District. Issue 1 (March 2021) - Han, Shumin; Han, Feng; Zhang, Shaojin; Li, Yuan; Zhang, Jiancai
Abstract: Rail transit has been playing a vital role in comprehensive transportation system, there goes without saying that rail transit will stimulate economic growth of the regions alongside railway lines, its coverage and development pattern will exert widespread and far-reaching impact on the area where railway travels through. In Xi'an-Yinchuan High-speed Railway construction setting, firstly, building an accessibility model based on the GIS platform and comparing analysis of traffic accessibility changes in the study area before and after the opening of the high-speed rail. Secondly, relying on the railway network and economic relations to establish comprehensive indicators System, build a coupling model of rail transit and regional economy in Shanxi-Gansu-Ningxia. Finally, predicting the coupling relationship between economy and transportation after the opening of high-speed rail. The experimental results show that the accessibility of cities along the line changes greatly before and after the completion of the high-speed rail. The high-speed rail line obviously promotes the economic development of the old revolutionary areas and surrounding cities along the line, and provides guiding suggestions for further improving the rapid railway network.